Use of the IRaMuTeQ software for the analysis of the reasons for the use of the Yape electronic wallet - Cieza-Villavicencio, Jonathan Scott (2024)
Over the years, technology has been gaining a preponderant role in society. The digital transformation, accelerated by the COVID-19 pandemic, has redefined business models that previously seemed solid. In this context, in Peru, an electronic wallet called Yape has managed to grow significantly in terms of users and market position, reduce the use of cash, contributing to banking access and the consequent reduction of informality. This study analyzes the reason for the acceptance of Yape versus other competitors in the market by applying the UTAUT2 model and the IRaMuTeQ software. The results show a strong relationship between the success of Yape with its speed and ease of use.